Study an Improvement of Electrostatic Prescipitator (ESP) Interference Protection Systems PLTU Pangkalan Susu Units 1 and 2 - Rikky Ferdinand Sinurat; Solly Aryza; Adi Sastra P. Tarigan (CERED Indonesia Institute, 2022)
The problem of air pollution in this technological era has reached an alarming level. This is in line with the increasing number of pollutants produced from daily activities. Some industrial factories, power plants, and motorized vehicles that every day always produce harmful pollutants that pollute clean air. Coal-fired power plants could be a source of air pollution if coal combustion was not handled properly. Where the ash from coal combustion in the boiler produces fly ash and bottom ash. Based on these conditions, a tool is needed to reduce or control fly ash. This study describes the reliability of the equipment in the generating unit so that the reliability of the ESP system can be guaranteed and maintained. With the results of cases that occurred in ESP during the review, 90% of the problems in ESP were found in ESP. This problem is closely related to other equipment which can later cause the ESP field to stop. It is necessary to pay attention to the readiness of the inside for the long term because the repair process takes a long time and when the unit is off (offline). To minimize problems on the inside, we can monitor the ESP performance chart itself by paying attention to the points in the cases described above. It is recommended that the inner parts such as stopper plates, etc., which are related to the mounting parts are expected to be welded to avoid loss. we can monitor the ESP performance chart itself by paying attention to the points in the cases described above. It is recommended that the inner parts such as stopper plates, etc., which are related to the mounting parts are expected to be welded to avoid loss. we can monitor the ESP performance chart itself by paying attention to the points in the cases described above. It is recommended that the inner parts such as stopper plates, etc., which are related to the mounting parts are expected to be welded to avoid loss.